The Overlooked Collection: The Ancient Art Collection of the Princes Czartoryski Museum .......... 143 - Gorzelany-Nowak, Dorota (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
Without a doubt, the Princes Czartoryski Museum’s position amongst Polish museum institutions is significant both because of its history and on account of its collections. The collection of paintings, graphics, arts and crafts and armaments was supplemented by ancient artefacts thanks to Prince Władysław Czartoryski, who, by working on the premise of a ‘scientific establishment’, was acquiring them in the second half of the 19th century. Those works of art were included in the permanent exhibition, since for Czartoryski and the Museum’s management at that time, the status of those objects as representing the development of art history was obvious. This changed after WW2 with the institution’s incorporation into the National Museum of Kraków in line with the policy then of eliminating private ownership and when the permanent exhibition was reorganised. As a result, ancient art disappeared from the exhibition’s scenario despite the enlargement of the exhibition space. Following the exhibition curator’s long efforts to organise a permanent exhibition, it became possible to display the antique collection in the Princes Czartoryski Museum’s Arsenal. The paper includes an analysis of the situation of the persistent exclusion of this part of the Museum’s collection within a wider exhibition, promotion and substantive context.